Manifestations of the pediatric multisystem inflammatory syndrome temporally related with SARS-CoV-2 (PIMS) in the gastrointestinal, cardiovascular, nervous and respiratory systems - Brzyska, Anna; Bogucka, Julia; Bojarska, Małgorzata; Domańska, Natalia (Journal of Education, Health and Sport, 2022)
Introduction and objective: The course of the pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS) is not fully understood. In most cases, complications are so severe that the patients require hospitalization. The aim of this study is to discuss the most common symptoms in the course of PIMS in the individual systems. Review methods: The Medline database (Pubmed) was searched in March 2022 using the keywords: PIMS symptoms, MIS-C manifestations, hyperinflammation, post-COVID. English and Polish language papers published between 2020 and 2022 were selected. Brief description of the state of knowledge: Studies show that the most frequently occuring symptoms are fever, followed by gastrointestinal manifestations. However, the most serious complications have been reported in thecardiovascular system. It is estimated that up to half of the patients develop left ventricular failure or shock, and a quarter may develop coronary artery aneurysms. A large percentage of patients diagnosed with PIMS also manifest nervous system symptoms. In addition to symptoms, organic brain lesions have been described in imaging studies. In contrast to COVID-19 disease, respiratory complications are rare in PIMS. Respiratory failure, if present, usually develops secondary to cardiovascular failure. Summary: The current reports allow to state that PIMS is a rare, but serious disease affecting children most often in school age. Symptoms are not specific and may be different for each patient. Since the disease is difficult to diagnose, criteria have been developed that include the most common symptoms as well as a link to SARS-CoV-2 exposure. Key words: PIMS symptoms; MIS-C manifestations; hyperinflammation; post-COVID